Robbery - Baker, Stanley 1928-1976; Pettet, Joanna 1942-; Geeves, David 1927-2005 (Studio Canal, 2008)
"Inspired by true events (The Great Train Robbery of 1963) Robbery is an uncompromising portrayal of swinging London's criminal underworld. Ouintessentially British and with a documentary style commitment towards accuracy, Robbery mixes meticulously constructed, high octane action sequences (including one of the most nerve shattering - and often replicated - car chases seen on film) with taut suspense and gritty realism, making it the groundbreaking template for future crime dramas such as The French Connection, The Long Good Friday and TV series The Sweeney. Starring Stanley Baker, Frank Finlay, Barry Foster and William Marlowe, Robbery is an entertaining and archetypal entry into the genre of British Gangster Movies."
Feature aspect ratio : 1.33:1 (4:3)
Originally produced as a motion picture in 1967
Verlagsnummer OPTD1134
Keywords: Train robberies / Great Britain / Drama; Train robberies; Great Britain / https://id.oclc.org/worldcat/entity/E39PBJdmp7p3cx8hpmJ8HvmTpP; Crime films; Drama; Feature films; Gangster films; Film; DVD-Video